Penerapan Latihan Model Dhin Dhon Pada Klub Bolavoli Di Kabupaten Bantaeng - Sahabuddin Sahabuddin; Hikmad Hakim (Lembaga Layanan Pendidikan Tinggi Wilayah IX Sulawesi, 2020)
Abstract This service aims to socialize and implement dhin dhon model exercises at the volleyball club in Bantaeng Regency. This community service is one part of the Tri darma of higher education that is required for Lecturer staff at Makassar State University. The object of this service is the volleyball athlete in Bantaeng Regency. The implementation technique of the socialization and application of dhin dhon training for athletes is through the provision of theory and practice of the forms of dhin dhon training model movements and other related sciences in this community service. The implementation of socialization activities under the model of passing exercises (dhindhon) in the volleyball game in Bantaeng Regency can be concluded as follows: (1) In general, the socialization participants were very enthusiastic in accepting the material provided both in theory and practice, (2) Participants could realize that for get maximum skills or skills required training programs with a variety of methods and models of training that are carried out systematically and programmed, and (3) The dissemination of the model of passing training (dhindhon) in the game of volleyball is very helpful to achieve technical skills to the maximum which is only done conventionally without the creativity and innovation of each exercise. Abstrak Pengabdian ini bertujuan untuk mensosialisasikan dan menerapkan latihan model dhin dhon pada klub bolavoli di Kabupaten Bantaeng. Pengabdian masyarakat ini adalah salah satu bagian dari pada Tri darma perguruan tinggi yang diwajibkan bagi staf Dosen di Universitas Negeri Makassar. Objek dari pengabdian ini adalah atlet bolavoli di Kabupaten Bantaeng. Teknik pelaksanaan dari pada sosialisasi dan penerapan latihan dhin dhon bagi atlet adalah melalui pemberian teori dan praktek tentang bentuk-bentuk gerakan latihan model dhin dhon serta ilmu pengetahuan lain yang terkait dalam pengabdian masyarakat ini. Pelaksanaan kegiatan sosialsiasi model latihan passing bawah (dhindhon) dalam permainan bolavoli di Kabupaten Bantaeng dapat ditarik kesimpulan sebagai berikut: (1) Pada umumnya peserta sosialisasi sangat antusias dalam menerima materi yang diberikan baik secara teori maupun praktek, (2) Peserta dapat menyadari bahwa untuk mendapatkan keterampilan atau skill yang maksimal dibutuhkan program latihan dengan berbagai metode dan model latihan yang dilakukan secara sistematis dan terprogram, dan (3) Adanya sosialisasi model latihan passing bawah (dhindhon) dalam permainan bolavoli sangat membantu untuk mencapai keterampilan teknik secara maksimal yang selama hanya dilakukan secara konvensional tanpa adanya kreatifitas dan inovasi setiap latihan.